Use of weapons - Banks, Iain, 1954- (London : Orbit, 2011)
Cheradenine Zakalwe, a retired agent for Special Circumstances--which alters the fate of planets for the benefit of the Culture--is pulled back into service by Diziet Sma for one more mission with vast political consequences while the drone called Skaffen-Amtiskaw pursues its own agenda.
Adult.
Adult
Keywords: Life on other planets -- Fiction; Space warfare -- Fiction; Life on other planets -- Fiction; Science fiction; Space warfare -- Fiction; Science fiction